Sedimentological analysis of marine deposits off the Bagnoli-Coroglio Site of National Interest (SNI), Pozzuoli (Napoli) Bay. Issue 6 (2nd July 2020) - Molisso, Flavia; Caccavale, Mauro; Capodanno, Monica; Di Gregorio, Costantino; Gilardi, Mauro; Guarino, Antimo; Oliveri, Elvira; Tamburrino, Stella; Sacchi, Marco
ABSTRACT: We present the results of a sedimentological and mineralogical study conducted on 305 marine sediment samples (32 seafloor grab samples and 273 subsea floor samples from 91 vibrocores) collected in the marine area of the eastern Pozzuoli Bay, offshore the area of Bagnoli, that has been the site of heavy industrial activity for more than a century. The coastal (onland-offshore) area of Bagnoli–Coroglio has been recognised as a contaminated Site of National Interest (SNI) by the Italian Ministry of the Environment (2000–2001) and since then it has been the subject of a series of environmental studies that have documented a severe contamination of soils onland and marine sediments offshore. Based on the outcomes of the sedimentological classification discussed in this study we have constructed a series of thematic maps illustrating the areal distribution of the sedimentary facies at different stratigraphic levels. Our interpretation provides a support in reconstructing the complex set of environmental changes that have affected the offshore of the eastern Pozzuoli Bay prior to and after the termination of the industrial activity of the Bagnoli brownfield.